Immunoelectron microscopy of acute graft versus host disease of the skin after allogeneic bone marrow transplantation. Issue 9 (September 1993) - Takata, M; Imai, T; Hirone, T
Abstract : AIMS–To clarify the pathological mechanisms of acute cutaneous graft versus host disease (GvHD) following allogeneic bone marrow transplantation. METHODS–Skin biopsy specimens from five patients were examined by immunoelectron microscopy. A panel of monoclonal antibodies against T cell and natural killer cell subpopulations was used, including anti-CD4, -CD8, -CD16b, -CD56, -CD57, and -TCR delta 1 antibodies. RESULTS–All the specimens contained CD8+ cells, CD4+ cells, and CD56+ cells infiltrating the epidermis. Cells stained with anti-CD16b, -CD57, or -TCR delta 1 were very sparse or absent. Most of the CD8+ cells in the epidermis displayed morphological features of activated cytotoxic T lymphocytes and apposition of such cells to degenerating keratinocytes was shown. CD4+ cells outnumbered CD8+ cells in the epidermis in all five cases. Noticeable intercellular as well as intracellular oedema of keratinocytes was observed at the site of prominent CD4+ cell infiltration, suggesting that these also have a role as actual effector cells by secreting cytotoxic cytokines. CD56+ cells infiltrating the epidermis did not exhibit the characteristic ultrastructural morphology of the natural killer cells thus far examined, and their lineage remained uncertain. CONCLUSIONS–These data provide direct evidence that CD8+ cytotoxic T cells attack keratinocytes, and further suggest that CD4+ cells as well as CD56+ cells participate in the cellular pathogenesis of acute cutaneous GvHD.